Interaction of isoflavones with different structures and transferrin. Issue 9 (20th October 2016) - Zhang, Xiu-feng; Sun, Xin; Liu, Yong-guang; Han, Rui-min; Lan, Ling; Chen, Hong-bo; Sun, Xiao-ran; Li, Qian; Tang, Ya-Lin
ABSTRACT: Transferrin, as a drug carrier, holds promise for targeted drug delivering into cancer cells where transferrin receptors (TfRs) are overexpressed. In the present study, the influence of structure characteristics of isoflavones have been explored, which are critical for binding to transferrin. Three isoflavones, daidzein, puerarin, and genistein, with characteristic daidzein core structures were selected for the study of the effects of substituent group on the A-ring on interaction with transferrin. The results demonstrated that daidzein-bound transferrin with an affinity almost 7 or more than 20 times higher than that of puerarin or genistein attributed to the addition of C(8)-glycosyl or C(5)-hydroxyl on the aromatic A-ring. Our docking study indicated that daidzein had strong hydrogen bond and hydrophobic interactions with transferrin, which believed to contribute to its higher binding affinity. Furthermore, daidzein binding induced fewer structures changes of transferrin than that by puerarin or genistein, suggesting that daidzein binding result in less disturbance of normal biological function of transferrin. Together these findings not only corroborated that daidzein was a superior ligand for transferrin, but also provided substantive information for possible modification and design methods of isoflavone.